SPATIO-TEMPORAL CORRELATIVE MODELLING OF DENGUE CASES IN SELANGOR, MALAYSIA - THIRUCHELVAM, LOSHINI (2020)
This study aims to investigate the relationship of dengue cases with Air Pollution Index (API), climate variable (represented as mean temperature, relative humidity and cumulative rainfall parameters) and spatial effects (represented as neighbouring regions‟ dengue models).